Today we die a little! : the inimitable Emil Zátopek, the greatest Olympic runner of all time - Askwith, Richard (Nation Books, 2016)
"Based on extensive research in the Czech Republic, interviews with people across the world who knew him, and unprecedented cooperation from his widow ... journalist Richard Askwith's book breathes new life into the man and the myth, uncovering a glorious age of athletics and an epoch-defining time in world history"--Dust jacket flap.